A protocol of randomized controlled trial for Modified Xiaoyao Powder in the treatment of chronic obstructive pulmonary disease combined mild to moderate depression. Issue 47 (20th November 2020) - Chen, Keling; Zhao, Keni; Wang, Wujun; Xiao, Wei; Xiao, Jing; Yang, Yang; Liu, Yufei; Xie, Xiaohong
Abstract: Introduction: Depression is an important complication of chronic obstructive pulmonary disease (COPD), occurring in more than one-third of individuals with COPD, and its severity is closely related to the severity and acute exacerbation of COPD, significantly contributing to the risk of death from COPD. Comorbid depression in COPD can be a burden on COPD-related diseases by reducing quality of life and compliance with treatment. Unfortunately, symptoms of COPD combined anxiety and depression are not properly diagnosed and treated in clinical practice, especially in the early stages of mood changes in patients with COPD, as the symptoms are mild and monotonous, and are overlooked. Methods: In this prospective, randomized, placebo-controlled trial, we will assigned 280 eligible patients who had COPD combined depression to receive either Modified Xiaoyao Powder (MXP) or placebo. The primary end point is the change in the Hamilton Depression Scale (17 items) (HAMD-17) score from baseline on weeks 4, 12, and 24. Discussion: Six months of MXP for COPD combined mild to moderate depression may alleviate the symptoms of depression, reduce the frequency of hospitalizations, the number of exacerbations, and improve the compliance of treatment. Trial registration: ChiCTR2000038741. Abstract : Supplemental Digital Content is available in the text